Metal–Organic Framework Mediated Cobalt/Nitrogen‐Doped Carbon Hybrids as Efficient and Chemoselective Catalysts for the Hydrogenation of Nitroarenes. Issue 10 (24th April 2017) - Sun, Xiaohui; Olivos‐Suarez, Alma I.; Oar‐Arteta, Lide; Rozhko, Elena; Osadchii, Dmitrii; Bavykina, Anastasiya; Kapteijn, Freek; Gascon, Jorge
Abstract: A Co@N‐doped carbon (Co@NC) hybrid was synthesized by thermal decomposition of the metal–organic framework (MOF) ZIF‐67 under N2 atmosphere. These hybrid materials exhibit outstanding catalytic activity and chemoselectivity for the conversion of a wide range of substituted nitroarenes to their corresponding anilines under relatively mild reaction conditions. The high catalytic performance is attributed to the formation of cobalt nanoparticles and to the presence of atomically dispersed Co species in close interaction with nitrogen‐doped graphene. Both active species are formed in situ during the pyrolytic transformation of ZIF‐67. The catalysts could be reused in consecutive runs, exhibiting a slightly lower activity ascribed to blockage of the active sites by strongly adsorbed reaction species. These results open up a pathway for the design of noble‐metal‐free solid catalysts for industrial applications. Abstract : A hybrid for hydrogenation : The one‐step thermal decomposition of the metal–organic framework ZIF‐67 under a N2 atmosphere is a straightforward approach to synthesize a scalable, recyclable, and active heterogeneous catalyst for the hydrogenation of nitroarenes. The resulting cobalt‐containing carbon composites exhibit an excellent catalytic performance in the hydrogenation of a wide range of nitroarenes to their substituted anilines under relatively mild conditions.